โครงสร้างจุลภาคในสภาพหล่อและโครงสร้างจุลภาคภายหลังฝ่านกระบวนการอบให้เป็นเนื้อเดียวของโลหะผสมอะลูมิเนียมความแข็งแรงสูงพิเศษ (A1-10Zn-1-2.5Mg-1-2.3Cu-0.14Zr) ที่หล่อด้วยกระบวนการ Direct Chill ภายใต้การกวนของแม่เหล็กไฟฟ้า - แขขวัญ โก๊สุโข (จุฬาลงกรณ์มหาวิทยาลัย, 2007)
As-cast and homogenized microstructures of Al-10Zn-Mg-Cu-Zr alloys were studied to understand microstructure constituents’ formation of super high strength aluminum alloys. Ingot with diameter of 200 mm was cast by low frequency electromagnetic direct chill casting. The Zn content of the sample were 10% and Mg content were 1.0~2.5 wt% and Cu content were 1.0~2.3 wt%. OM and SEM were used for microstructure observation and phase’s identification was done by using XRD, EDX and EPMA. Al+ (MgZn2) included T (Mg32(Al,Zn)49 or S (Al2CuMg) phases in lamellar form of eutectic were found in as-cast microstructure of 2.5Mg2.3Cu and 2.5Mg1.0Cu alloys. T (Mg32(Al,Zn)49 and S (Al2CuMg) phases were not detected by X-Ray Diffraction method in 2.5Mg1.5Cu, 1.5Mg2.3Cu and 1.0Mg2.3Cu alloys. Al7Cu2Fe phase was found in every alloy compositions. When the amount of Mg and Cu were decreased, the amounts of eutectic phases were also decreased. For the homogenized samples, the dissolution of the eutectic structures were observed. Al7Cu2Fe compound still remained after along homogenization time. Eutectic phases also remained but only a small fraction.